Deteksi Antibodi dan Isolasi Toxoplasma gondii pada Itik lokal di Bali (DETECTION ANTIBODIES AND ISOLATION OF TOXOPLASMA GONDII IN DOMESTIC DUCK IN BALI ) - Dwinata, Made; Oka, Ida Bagus Made; Damriyasa, I Made (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
This study was performed to determine detection antibodies and isolation T. gondii infection in domestic duck in Bali. A total, 188 domestic ducks sera were examined using indirect haemaglutination test  kit (IHA). Heart, brain and muscle of seropositive IHA test were used for isolation with pepsin-HCL digestion and bioassay in mice and cat.  The result of these research showed that  47 (25%) ducks were found to be positive for T. gondii antibodies at the cut-off  e” 1:64. The seroprevalence in male and female duck were 27,8% and  22,4% respectively, however, statistical analysis showed that the difference was not significant (P>0,05). The seroprevalence in cage and free-range duck were 18,7% and 29,2% respectively, but the difference was not statistically significant (P>0,05).  The antibodies titer  ranging from 1:64 to 1:2048.  Also, viable T. gondii was isolated from seropositive duck by bioassay mice and cat. Most of the isolated strains were avirulent to mice. This study showed that domestic duck could have a potensial role in transmitting toxoplasmosis to human in Bali.